2016
DOI: 10.18174/393409
|View full text |Cite
|
Sign up to set email alerts
|

On farm development of bedded pack dairy barns in The Netherlands : gaseous emissions bedding

Abstract: Summary UK Gaseous emissions of four bedded pack dairy farms were measured using the flux chamber method.One used wood chips as bedding material, the other three used compost of green waste. Emissions of ammonia per m 2 bedding area were considerably lower compared to the concrete slatted floor housing system that acted as a reference system. Due to large area per cow the emissions per cow were however 175%-475% higher compared to the reference system. Emissions of nitrous oxide (N2O)were 3.5 to 25 times highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The fourth cluster is composed of materials with particle sizes of 4 to 16 mm. The conventional material in this group is wood chips (Van Dooren et al, 2016;Smith et al, 2017;Van Dooren et al, 2018), and the alternative bedding materials include bark mulch, conifer forest litter, P. oceanica, and triticale husks. In this group, 42% of the P. oceanica particles were in the size range of 8 to 16 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth cluster is composed of materials with particle sizes of 4 to 16 mm. The conventional material in this group is wood chips (Van Dooren et al, 2016;Smith et al, 2017;Van Dooren et al, 2018), and the alternative bedding materials include bark mulch, conifer forest litter, P. oceanica, and triticale husks. In this group, 42% of the P. oceanica particles were in the size range of 8 to 16 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of forming nitrous oxide in litter-based systems should be considered. With bedded pack barns nitrous oxide emissions were measured to be 3 to 26 times higher than the reference system (a concrete slatted floor with slurry storage in a pit underneath the floor) (van Dooren et al 2016). The research by WUR showed that wood chips for composting is better than composted manure in terms of animal welfare and emissions from the barn.…”
Section: Application Of Bedding Materials (Eg Sand)mentioning
confidence: 87%
“…Low rate slurry aeration causes a reduction in chemical reaction and prevent crust formation in the slurry pit. This method is now tested in the Netherlands and a study carried out by van Dooren et al (2019a) showed that daily mixing of slurry either with air pumped into the slurry or with an electrical mixer did not result in reduction of ammonia emission. However, Calvet et al (2017) explained a reduction in the emission of CH4 by 40%.…”
Section: Manure Aerationmentioning
confidence: 99%
“…The risk of forming nitrous oxide in litter-based systems should be considered. With bedded pack barns nitrous oxide emissions were measured to be 3 to 26 times higher than the reference system (a concrete slatted floor with slurry storage in a pit underneath the floor) (van Dooren et al, 2016). The research was done in WUR showed that wood chips for composting are better than composted manure in terms of animal welfare and emissions from the barn.…”
Section: Litter-based Systemsmentioning
confidence: 95%